Pyelocaliceal duplication with implantation of ectopic ureter in external genitalia as a cause of urinary incontinence in girl - Martins, Priscila; Morgato de Mello Miyasaki , Andrea; Silva Parreira, Ricardo; Basso, Mauro Roberto (Cirugía del Uruguay, 2025)
Although uncommon, ureteral duplication is the most common anomaly of the upper urinary tract, with a reported incidence of up to 4% of the population. It may present with ureteroceles and/or ectopic ureters, generally inserted in the proximal urethral region and less commonly, in the vagina. Clinical manifestations include urinary tract infections or urinary incontinence, depending on the position of the ectopic ureter and diagnosis is early. We report the case of a 5-year-old girl with complete ureteral duplication and urinary incontinence due to implantation of the ectopic ureter in the external genitalia. The treatment established was surgical, with uretero-ureteroanastomosis and resolution of the complaint of urinary incontinence in the postoperative period.